Deliberative Policy Approaches to Conflict Resolution in Coastal Shrimp Farming Governance: Evidence from Madura - Mohammad Baladdudin Dayar; Wilda Rasaili; Zarnuji; Hasan Muchtar Fauzi (Universitas Merdeka Malang, 2026)
Shrimp farm management in coastal areas often causes conflicts of interest involving local governments, shrimp farm entrepreneurs, local communities, and environmental groups. Social stability is also disrupted because shrimp farm management causes environmental pollution, damage to marine ecosystems, which results in the loss of livelihoods for coastal communities, and environmental disturbances caused by continuously running aerators. This study aims to formulate deliberative policy strategies to resolve conflicts of interest and social instability in shrimp farm management. The method used is qualitative descriptive with a case study approach. This study involved 9 institutions with 15 informants with data collection through observation, interviews, and documentation. Data were analyzed through interview transcription, theme categorization, and pattern identification. The data were presented in the form of analysis metrics, descriptions, and data visualization using NVivo Pro 12. The results of the study show that shrimp farm management involves many actors and has a significant impact on the environment, society, and economy. Local government deliberative policies are a solution-oriented and progressive strategy to prevent conflict and harmonize the interests of actors. The research findings were explored further by interpreting the issues and reinforcing the importance of shrimp farm management practices and consultations involving local government to harmonize interests. However, public involvement in planning needs to be optimized so that solutions are more effective and conflicts are resolved quickly.